THE EFFECT OF PRODUCT QUALITY, SERVICE QUALITY, AND TRUST ON CUSTOMER SATISFACTION AT PRAJA DECORATION IN PURWODADI - Ihsan Fauzi Ardiansyah; Abdulah Zailani; Zandra Dwanita Widodo (Yayasan Education and Social Center, 2023)
The following are some of the goals that were hoped to be accomplished as a result of the findings of this research: (1) To discover both partially and simultaneously the effect that trusts, product quality, and service quality have on consumer satisfaction. (2) To identify the factor that has the most significant influence on the level of contentment experienced by customers. This research was conducted on Praja Decoration consumers/customers in Purwodadi City. Based on Roscoe's general reference (1975) quoted by Sekaran and Wiley (2016, p. 264), the samples used in this study were as many as 40. The sampling technique was carried out by random sampling. According to the findings of the research, there is an influence on consumer satisfaction that is both partially and simultaneously contributed by the quality of the product, the quality of the service, and trust. Product quality is the most dominant variable, followed by service quality and trust variables. The magnitude of the influence of product quality, service quality, and trust on consumer satisfaction is 83.10%. Other variables outside this research model explain the remaining 26.00%